Kontroversi Hukuman Mati dalam Sistem Peradilan Pidana Dilihat dari Perspektif HAM (Hak Asasi Manusia) dan Kriminologi - Karmila, Karmila; Arinda, Suci; Putri, Eka; Hutapea, Sintong Arion (Journal of Contemporary Law Studies, 2025)
The death penalty is the highest form of punishment in the criminal justice system in Indonesia which is still applied for various serious crimes, such as premeditated murder, narcotics crimes, and terrorism. However, its application raises various debates from the aspects of law, human rights, and effectiveness in crime prevention. This research aims to analyze justice and transparency in the judicial process of death penalty cases in Indonesia and assess its effectiveness as an instrument of law enforcement. The method used in this research is a literature study by analyzing various legal sources, academic journals, and reports from human rights organizations. The results show that the application of the death penalty in Indonesia still faces various challenges, including the potential for judicial error, discrimination against certain groups, and lack of transparency in the legal process and execution. In addition, there is no strong evidence to suggest that the death penalty is more effective in reducing crime rates compared to life sentences. This study suggests that Indonesia needs to re-evaluate its death penalty policy by considering the principles of justice, legal effectiveness, and human rights protection. Reforming the criminal justice system and implementing a moratorium can be the first step in creating a more just and transparent legal system.